Strengthening Religious Moderation Based on Islamic Social Finance in the One Stove Three Stone Concept in Dosay Village, Papua - Abdulloh, Muhammad; Kasdi, Abdurrohman (LPPM IAIN Kudus, 2024)
Religious moderation is a view of equality that is very necessary in an era of plurality, which is still considered trivial by many people, but is actually very necessary. The implementation of moderation with various differences in practice can be supported through Islamic social finance as a basis for proving concern and equality in a real impact on the social environment wrapped in the concept of one stove three stone as a slogan for the foundation of brotherhood in Papua. This study seeks to reveal the strengthening of religious moderation based on Islamic philanthropy in the concept of one stove three stone using a qualitative method with descriptive analysis from interviews and field observations with correlation between concept and reality of implementation. This study found that Islamic social finance in terms of practice is able to strengthen religious moderation in Dosay Village with the concept of local wisdom through programs that increase social interaction and harmony between religious communities which are acculturated with religious activities such as zakat for converts, infaq torch relay activities in events Muharram which is enlivened by all religious population entities, endowments for public facilities used by all religious people so that the values of moderation and care are within the practical scope in terms of Islamic social finance concept of one stove three stones.